2005
DOI: 10.3346/jkms.2005.20.1.105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Skin Color by Melanin Index According to Site, Gestational Age, Birth Weight and Season of Birth in Korean Neonates

Abstract: Human skin color shows variations throughout life and influenced by various factors such as race, sex, age and hormones. Since the development of spectrophotometer, many studies on human skin color have been done. However, few studies have been carried out to measure the skin color of neonatal infants. The aim of our study was to assess the variations in skin color according to site, gestational age, birth weight and season of birth in Korean neonates. A total of 447 healthy neonates (3 days after birth, 213 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Previous studies showed that a reflectance spectrophotometer could be used to determine melanin density in the skin of humans and mice (12,13,19). High L*-values indicate low levels of cutaneous melanin density (14). In fact, the L*-value (mean AE SD ¼ 68.94 AE 3.05) of the sole (sunlight-unexposed area) is higher than that (mean AE SD ¼ 59.14 AE 3.28) of the forehead (sunlightexposed area).…”
Section: Effects Of Sunlight Exposure-related Factors On Urinary 8-ohmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that a reflectance spectrophotometer could be used to determine melanin density in the skin of humans and mice (12,13,19). High L*-values indicate low levels of cutaneous melanin density (14). In fact, the L*-value (mean AE SD ¼ 68.94 AE 3.05) of the sole (sunlight-unexposed area) is higher than that (mean AE SD ¼ 59.14 AE 3.28) of the forehead (sunlightexposed area).…”
Section: Effects Of Sunlight Exposure-related Factors On Urinary 8-ohmentioning
confidence: 99%
“…L*-values obtained by using a reflectance spectrophotometer have been used as a digital marker of melanin density in the skin of Asians (14). L*-values of a sunlightunexposed area (sole) are thought to correspond to the constitutive cutaneous melanin density in each individual, and L*-values of a sunlight-exposed area (forehead) are thought to correspond to the sunlight-mediated increase in cutaneous melanin density in addition to the constitutive melanin density.…”
Section: Cancer Epidemiol Biomarkers Prev; 20(8) August 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Byard (1981, p. 132) noted that the fact that samples of different age composition have been compared has contributed to a ''confusing picture of sex differences in pigmentation'' (see also Kalla 1973Kalla , 1974. We acknowledge that we are relying on other authors' statements that their subjects are adults, and that our decision to exclude children and teenagers caused us to discard a good number of papers (e.g., Byard and Lees, 1982;Carbonnel and Olivier, 1966;Chamla and Demoulin, 1978;Clark et al, 1981;Conway and Baker, 1972; Greksa, 1998a,b;Harrison and Owen, 1964;Harrison and Salzano, 1966;Harrison et al, 1967;Harvey and Lord, 1978;Hulse, 1967Hulse, , 1973Kalla, 1973;Kalla and Tiwari, 1970;Lasker, 1954;Ojikutu, 1974;Omoto, 1968;Park and Lee, 2005;Relethford et al, 1985;Rebato et al, 1993;Smith and Mitchell, 1973;Sunderland and Coope, 1973;Sunderland and Woolley, 1982;Walsh, 1963; Wasserman and Heyl, 1968;Weiner et al, 1963). Our sample is smaller than that used by Relethford (1997Relethford ( , 2000 because he used male-only data sets, and we excluded papers which only reported data on one gender or which pooled male and female data (Bü chi, 1957(Bü chi, /1958Caro, 1980;Das and Mukherjee, 1963;Ducros et al, 1975;Eriksson et al, 1980;Garrard et al, 1967;Harrison and Owen, 1964;…”
mentioning
confidence: 99%
“…Unfortunately, we had smaller numbers of reflectance values from the published data using all three Photovolt tristimuli, and not enough papers to work with the red, blue, and green Photovolt filters. We did not utilize more recent papers, which used yet other machines, as there are not enough data to do quantitative tests with them (Park and Lee, 2005;Parra et al, 2004;Shriver and Parra, 2000;Roh et al, 2001;Wu et al, 2001).To be considered for this paper, published data had to be taken at the inner face of the upper arm from adult (18 years or more) males and females within a certain population. Data on pregnant women were not included in our analysis, as pregnancy affects the skin color of women (Garn et al, 1956).…”
mentioning
confidence: 99%